IKLAN ANAK PRODUK MAKANAN DAN MINUMAN DI TELEVISI DAN ETIKA MEDIA DALAM PERSPEKTIF KEARIFAN LOKAL - Dian Marhaeni K. (Jurnal Ilmiah Komunikasi Makna, 2012)
Children advertising analysis of foods and beverage products in television in the reasearch to penetrated by media ethics and local wisdom. Theoretical framework used is media ethics theory. By using descriptive qualitative paradigm. The study of media texts will be done by frame of references of Jaksa dan Pritchard with fairness, accuracy and objectivity as media ethics theory. The second focus of analysis used by local wisdom of Javanese culture. The results showed that the theme of children advertising in television had not presented ethics media and local wisdom based Javanese culture wisdom. Children advertising of food and beverage to encourage instant foods.